Optimal care for mother and child: safety in obstetric anaesthesia - Chappell, Daniel; Neuhaus, Christopher; Kranke, Peter (Best practice & research. Clinical anaesthesiology, 2021)
Anaesthetists play a major role in the perioperative treatment of patients, sharing responsibility for quality and safety in anaesthesia, intensive care, emergency and pain medicine. Several aspects lead to the fact that these issues are particularly important in obstetric anaesthesia. As morbidity and mortality are dramatically higher than in a nonpregnant population in this age, there is room for improvement even in regions with a well-developed healthcare system. Adverse events and complications during birth often hit fast, hard and unexpectedly and require immediate patient-centred care. This mostly involves an interdisciplinary and interprofessional approach that includes obstetricians, neonatologists, anaesthetists, intensivists and of course midwives and nurses. In this article, established standards and emerging possibilities to improve patient safety by developing a culture of awareness for safety aspects, education, establishing safety and communication strategies and performing teamwork- and simulation training are discussed. Apart from these issues, self-care of clinicians is vital in the prevention of adverse events, because fatigue and burnout are associated with increased rates of complications.